The Differences between Using Quizizz Interactive Quiz And LiveWorksheet in Math Problem Solving Ability - Kowiyah; Mutiara Azzahra (LPPM Undiksha, 2022)
The problem in this research is the lack of students' ability to solve problems and the lack of use of interactive quizzes in learning. The purpose of this study is to analyse differences in the ability of students to solve math problems with Quizizz interactive quizzes and Liveworksheets. This research uses a quantitative research type using a Quasi Experiment approach. The data collection in this study used interviews and a problem-solving ability test in the form of open essay questions. This study sample is two class devided into an experimental class that will apply the Quizizz interactive quiz and an experimental class that will apply the interactive Liveworksheet quiz. The data analysis of this research was started by using validity test, reliability test, discriminatory power test, difficulty level test, normality test, homogeneity test, and hypothesis testing on Post-Test questions. The results showed Post-Test data using the Liveworksheet interactive quiz, the average score obtained was 22.8, while the class using the Quizizz interactive quiz had an average of 19.4. It can be concluded that the Liveworksheet interactive quiz is better than the one using the Quizizz interactive quiz, because it can make it easier for students to use it when understanding the material and working on essay questions, besides that students are more enthusiastic about working on questions because they are competing to get the highest score, and students are able to develop mathematical problem solving to improve their way of thinking.